High-strength corrosion-resistant die-casting Al-Mg-Si-Fe-Ti-Re alloy and preparation method thereof
By regulating the composition of Al-Mg-Si-Fe-Ti-Re alloy and using composite microalloyization methods and heat treatment processes, the problems of poor casting performance of Al-Mg alloy and insufficient strength of Al-Si alloy are solved, and die-cast aluminum alloy with high strength and good corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411895352.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-21
- Publication Date
- 2025-04-18
AI Technical Summary
In the prior art, the casting performance of Al-Mg alloy is poor, with poor fluidity and incomplete filling. At the same time, the strength of Al-Si alloy is low, lacks reinforced phases, and there is little research on corrosion of die-cast aluminum parts in China.
By regulating the alloy composition, a high-strength, corrosion-resistant die-cast Al-Mg-Si-Fe-Ti-Re alloy is developed, and composite microalloyization methods and supporting heat treatment processes are used, combined with ultrasonic mixing and die-casting processes to improve the fluidity and strength of the alloy.
The uniform corrosion behavior of the alloy and good intergranular corrosion resistance are achieved, while improving the fluidity and strength of the alloy, solving the problems of casting performance and strength.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material manufacturing, and specifically relates to a high-strength and corrosion-resistant die-cast Al-Mg-Si-Fe-Ti-Re alloy and a preparation method thereof. Background Art
[0002] 5xxx aluminum alloy is widely used in automobiles, shipbuilding, aircraft and spacecraft due to its lightweight, medium strength and good corrosion resistance. 5xxx aluminum alloy is the most resistant to acid and alkali corrosion among the 8 aluminum alloy series, which makes 5xxx aluminum alloy suitable for environments that most aluminum plates cannot adapt to. Among them, in terms of marine aluminum alloys, 5xxx aluminum alloy has an absolute advantage with its excellent corrosion resistance, high formability and weldability. 5xxx aluminum alloy is Al-Mg alloy. The main 5xxx aluminum alloys currently used in ships are AA5052, AA5454, AA5083 and AA5383. However, the casting performance of Al-Mg alloy is not as good as that of Al-Si alloy, and there are problems such as poor fluidity and incomplete filling.
[0003] Die-casting technology is widely used in the automotive and shipbuilding fields due to its high production efficiency, good surface and dimensional accuracy of parts, and suitability for mass production. Al-Si alloys have good die-casting performance and are often used as raw materials for die-casting aluminum alloys. The main aluminum alloys currently used for die-casting production are: ADC12, A356, A380, A390, and YL112. However, the strength of Al-Si alloys is relatively low, generally less than 300Mpa, and lacks strengthening phases. At present, there are few domestic reports on the corrosion of die-cast aluminum parts, and there is a lack of research on the factors affecting the corrosion of conventional die-cast aluminum alloy materials and their mechanism analysis.
[0004] Due to the potential difference between the precipitated phase and the aluminum matrix in the aluminum alloy, a large number of micro galvanic cells are formed at the grain boundaries, causing the precipitated phase to be preferentially corroded in the corrosive solution. The present invention aims to regulate the alloy composition on the basis of aluminum-magnesium alloy and develop a die-casting aluminum alloy with high strength, good corrosion resistance and fluidity. Summary of the invention
[0005] The object of the present invention is to overcome at least one disadvantage of the prior art and to provide a high-strength, corrosion-resistant die-cast Al-Mg-Si-Fe-Ti-Re alloy and a preparation method thereof.
[0006] The technical solution adopted by the present invention is: In a first aspect, the present invention provides a high-strength, corrosion-resistant die-cast Al-Mg-Si-Fe-Ti-Re alloy, which comprises the following composition, in mass percentage: Mg 8.0-9.0%, Si 2.5-3.5%, Fe 0.3-0.5%, Ti 0.1-0.2%, Sn 0.2-0.4%, Bi 0.05-0.15%, Re 0.3-0.5%, and the balance is Al and unavoidable impurities.
[0007] In some examples, the alloy includes the following rare metals by mass percentage: Ir 0.2-0.4%, Ta 0.3-0.5%, Te 0.05-0.15%.
[0008] In some examples, the alloy includes the following rare metals by mass percentage: Ho 0.3-0.5%, Tb 0.05-0.15%.
[0009] In a second aspect, the present invention provides a method for preparing the Al-Mg-Si-Fe-Ti-Re alloy according to the first aspect, comprising the following steps: 1) Melt: After melting the ingredients according to the alloy composition, a covering agent and a degassing agent are added to obtain a melt 1; 2) Ultrasonic mixing of melt: melt 1 from step 1) is added with the composite carbide preform, and then subjected to ultrasonic vibration for 0.5 to 1 h to obtain melt 2; 3) Ingot casting treatment: taking the melt 2 and performing die casting treatment, solution treatment and aging treatment to obtain the high-strength and corrosion-resistant die-cast Al-Mg-Si-Fe-Ti-Re alloy.
[0010] In some examples, the mass ratio of the composite carbide preform to the melt 1 in step 2) is 1:(19.5-20.5).
[0011] In some examples, the composite carbide prefabricated block added in step 2) is prepared as follows: 1) Cleaning: Mix TaC powder and HfC powder in a mass ratio of (0.95-1.05):1, perform alkali washing and acid washing in sequence, filter and dry to obtain composite carbide; 2) Iron plating: Fe 2 (SO 4 ) 3 9H 2 O solution, NaBH 4 The solution is heated and mixed to obtain a plating solution, and then NaHCO is added 3 The solution is stirred until the plating solution is clear, and then dopamine hydrochloride, composite carbide and HCHO solution are added to react for 30 to 60 minutes to obtain iron-plated carbide powder; 3) Ball milling mixed powder: ball milling the iron-plated carbide powder in step 2), then mixing it with aluminum powder, and drying to obtain a mixed powder of iron-plated carbide and aluminum powder, wherein the mass fraction of the iron-plated carbide powder is 15% to 20%; 4) The mixed powder in step 3) is subjected to spark plasma sintering and cooled to obtain a composite carbide preform having a size of φ20 mm×10 mm, and the density thereof is controlled between 85% and 90%.
[0012] In some examples, the particle size of the TaC powder used in step 1) is in the range of 1000-1400 mesh, wherein the particle size of the HfC powder is in the range of 900-1200 mesh.
[0013] In some examples, the casting temperature of the die casting process is 700-720°C.
[0014] In some examples, the solution operation is as follows: the solution temperature is 480-500°C, the heat preservation time is 8-12h, and then it is quickly placed in water with a temperature of 50-60°C for cooling.
[0015] In some examples, the aging treatment operation is: the aging treatment temperature is 140-160° C., the holding time is 6-8 h, and then air-cooled to room temperature.
[0016] The beneficial effects of the present invention are: The present invention implements effective and executable composite microalloying means and a matching reasonable heat treatment process system, combines the advantages of Al-Mg alloy corrosion resistance and Al-Si alloy casting fluidity, and develops a new alloy system. The new alloy can not only show uniform corrosion behavior and good intergranular corrosion resistance, but also increase the Si content, so that the alloy has good fluidity and complete filling, which greatly improves the casting fluidity of the alloy. Adding modified elements and introducing graphene in the die-casting process allows the alloy to maintain a higher strength.
[0017] In some embodiments of the present invention, low melting point elements are added to improve the casting fluidity of the alloy. The melting point of Bi is 271.3°C, and the melting point of Sn is 231.9°C. The melting point of the alloy is reduced, which can effectively reduce the temperature range of solid-liquid coexistence during die casting solidification. During the extrusion casting process, the liquid phase alloy flows faster under higher mechanical pressure and the degree of segregation is reduced. At the same time, the addition of Bi and Sn can promote the formation of active points on the surface of the aluminum alloy and the alloy surface, thereby improving the casting fluidity of the alloy, and can also reduce the tendency of thermal cracking during the solidification of the alloy, reduce the tendency of shrinkage and shrinkage, and improve air tightness.
[0018] In some embodiments of the present invention, the addition of Ir element can reduce the anodic activity of aluminum alloy, thereby improving the corrosion resistance of the alloy in seawater. The addition of Ir element can refine the aluminum alloy grains and provide nucleation cores for the precipitation phase, so that the precipitation phase gradually expands from the grain boundary to the matrix, making it more dispersed and uniform, reducing the electrode potential difference between the grain boundary and the grain, and improving the corrosion resistance of the alloy.
[0019] In some embodiments of the present invention, after adding a trace amount of Ta element, the self-corrosion potential of the alloy increases, the self-corrosion current density decreases, and the corrosion resistance is improved. The addition of Ta element reduces the anode activity of aluminum alloy. When the Ta content is 0.5%, the size of the primary α grain increases, the formation of corrosion galvanic cells is reduced, and the corrosion resistance of the aluminum alloy in seawater is improved. Ta can reduce the diffusion capacity of vacancies and solute atoms, and reduce the vacancy and solute concentration gradient from the grain boundary to the crystal, which narrows the width of the grain boundary non-precipitation zone, reduces the electrode potential difference between the grain boundary and the crystal, and improves the corrosion resistance of the alloy.
[0020] In some embodiments of the present invention, the Al 2 Te 3 phase as the nucleation core, which can effectively refine the alloy grain size. 2 Te 3 The melting point of the phase is higher than the preparation temperature of the alloy. During the solidification process, Al 2 Te 3 The phase will be crystallized and precipitated first, and exist in the aluminum melt in the form of particles as nucleation points, which increases the number of nuclei and achieves the effect of grain refinement. Some Te atoms are enriched at the front of the second phase crystallization to hinder its growth, so that it changes from a thick strip to a fine particle. The finer the grain size of the alloy, the more grain boundaries there are, and the higher the strength of the alloy. Te has a high potential, and adding it to the alloy can also improve the corrosion resistance of the alloy matrix.
[0021] In some embodiments of the present invention, when rare earth Ho is added to aluminum alloy, it can have a certain alloying effect, and the gas such as hydrogen and some non-metallic elements in the aluminum alloy have great affinity, which has a positive effect on dehydrogenation, refining and purification. Rare earth Ho also has a metamorphic effect, and some fine oxide inclusions can be effectively removed under the action of rare earth Ho, and the uneven second phase material at the grain boundary is basically dissolved into the matrix, and fine second phase particles are precipitated in the grains and at the grain boundaries.
[0022] In some embodiments of the present invention, the rare earth Tb has a strengthening effect on the tensile strength and toughness of the alloy. On the one hand, due to the modificatory effect of Tb, the alloy grains become finer, which can reduce the spacing of the secondary dendrite arms. At the same time, the rare earth Tb can also perform second phase pinning on the grain boundaries and dendrites, preventing the grains from growing in the subsequent heat treatment process.
[0023] Adding nano carbide TaC / HfC within a certain range, with the increase of nano particle content, the fine second phase particles cause a significant increase in the resistance to grain boundary migration, and the effect of inhibiting grain growth is enhanced. At the same time, high hardness TaC / HfC particles are dispersed in the alloy in a granular form, which hinders the movement of dislocations during plastic deformation and significantly improves the strength of the alloy. Adding an appropriate amount of TaC / HfC has the combined effects of fine grain strengthening and dispersion strengthening, effectively improving the room temperature mechanical properties of the alloy. DETAILED DESCRIPTION
[0024] The following disclosure provides many different embodiments or examples for implementing different solutions of the present invention.
[0025] Unless otherwise specified, the specific preparation method of the composite carbide prefabricated block used in each embodiment of the present invention is as follows: 1) Alkaline washing: Heat 300 mL of 0.5 mol / L KOH solution in a water bath. When the temperature rises to 95°C, add 50 g of TaC powder and HfC powder. The mass percentage of TaC powder and HfC powder is 1:1. Stir at this temperature for 30 min and filter. 2) Acid washing: Put the TaC powder and HfC powder after the previous step of alkaline washing into 0.1 mol / L HNO 3 Soak in the solution for 10 minutes, filter and dry; 3) Iron plating: 80 g Fe 2 (SO 4 ) 3 9H 2 O, 20 g NaBH 4 Add water to each solution to make 500 mL, heat to 75 °C, mix the two solutions, continue heating for 25 min, and add 5 mol / L NaHCO dropwise. 3 The solution was stirred until the plating solution was clear, and then 5 g of dopamine hydrochloride and 10 g of the above-mentioned acid-washed composite carbide were added. After the temperature was uniform, 100 mL of HCHO solution was added and reacted for 30 minutes to obtain some prepared iron-plated carbide powders; 4) Ball milling mixed powder: take the raw materials in step 3) and ball mill them for 6 to 8 hours under argon protection environment, the ball milling speed is 600 to 800 r / min, the ball-to-material ratio is 1:8, and 15% to 20% of the total weight of the raw materials is added as a grinding dispersant. After grinding, a mixed powder is obtained to obtain a composite powder of iron-plated carbide and aluminum powder, wherein the mass fraction of the iron-plated carbide powder is 15% to 20%; 5) Vacuum drying: the mixed powder after ball milling in step 4) is placed in a vacuum drying oven and dried at 60°C for 10 to 12 hours to remove the dispersant to obtain a dry mixed powder; 6) Spark plasma sintering: the composite powder of step 5) is placed in a graphite mold with a diameter of 20 mm, and spark plasma sintering is performed in a spark plasma sintering furnace under a nitrogen protective atmosphere. The sintering pressure is 50 MPa, the sintering temperature is 530 °C, the holding time is 6 min, and the furnace is cooled to prepare a number of composite carbide preforms with a size of φ20 mm×10 mm, and the density is controlled between 85-90%.
[0026] In some examples of manufacturing processes, the particle size of the TaC powder used in step 1) is in the range of 1000-1400 mesh, and the particle size of the HfC powder is in the range of 900-1200 mesh, forming a certain coarse and fine match between the two.
[0027] The technical solution of the present invention is further described below with reference to examples. In order to obtain a product with more stable quality, the impurities in each example are controlled to be below 0.25%.
[0028] Example 1 According to the weight percentage of the constituent elements, Mg: 8.5%, Si: 3.0%, Fe: 0.4%, Ti: 0.15%, Sn: 0.3%, Bi: 0.1%, and the balance is Al. The specific alloy preparation process is as follows: 1) According to the designed alloy composition, pure aluminum is first placed in a graphite crucible, and the temperature of the resistance furnace is set to 750°C. After the aluminum is completely melted, other intermediate alloys are added, and then the temperature of the resistance furnace is lowered to 710°C, pure magnesium wrapped in aluminum foil is added, and a layer of covering agent (KCl + NaCl, mass fraction 1:1) is sprinkled on it. After the pure magnesium is completely melted, hexachloroethane is added for degassing to obtain melt 1; 2) Take the melt 1 of step 1), add the composite carbide preform, the mass ratio of the preform to the melt 1 is 1:20, insert the ultrasonic vibrator 80 mm below the melt, start the ultrasonic vibration for 0.5 h to obtain the melt 2, the maximum amplitude of the ultrasonic vibration is 50 nm, and the vibration frequency is 20 kHz; 3) Take melt 1 and keep it warm for 10 minutes, pour it into the die-casting storage cylinder with a feeding spoon for die-casting, the pouring temperature is 700-720°C, the mold temperature is 180-200°C, the injection pressure is 85Mpa, the injection time is 3s, the cooling time is 2s, the mold retention time is 10s, and die-cast into aluminum alloy plate ingots; 4) subjecting the prepared alloy ingot to a solution treatment at a solution temperature of 480°C for 8 hours, and then rapidly cooling it in water at a temperature of 50-60°C; 5) The alloy ingot after solution treatment is subjected to aging treatment at a temperature of 150°C for 6 h, followed by air cooling to room temperature.
[0029] Example 2 According to the weight percentage of the constituent elements, Mg: 8.5%, Si: 3.0%, Fe: 0.4%, Ti: 0.15%, Ir: 0.3%, Ta: 0.5%, and the balance is Al. The specific alloy preparation process is as follows: 1) According to the designed alloy composition, pure aluminum is first placed in a graphite crucible, and the temperature of the resistance furnace is set to 750°C. After the aluminum is completely melted, other intermediate alloys are added, and then the temperature of the resistance furnace is lowered to 710°C, pure magnesium wrapped in aluminum foil is added, and a layer of covering agent (KCl + NaCl, mass fraction 1:1) is sprinkled on it. After the pure magnesium is completely melted, hexachloroethane is added for degassing to obtain melt 1; 2) Take the melt 1 of step 1), add the composite carbide preform, the mass ratio of the preform to the melt 1 is 1:20, insert the ultrasonic vibrator 80 mm below the melt, start the ultrasonic vibration for 0.5 h to obtain the melt 2, the maximum amplitude of the ultrasonic vibration is 50 nm, and the vibration frequency is 20 kHz; 3) Take melt 1 and keep it warm for 10 minutes, pour it into the die-casting storage cylinder with a feeding spoon for die-casting, the pouring temperature is 700-720°C, the mold temperature is 180-200°C, the injection pressure is 85Mpa, the injection time is 3s, the cooling time is 2s, the mold retention time is 10s, and die-cast into aluminum alloy plate ingots; 4) subjecting the prepared alloy ingot to a solution treatment at a solution temperature of 480°C for 8 hours, and then rapidly cooling it in water at a temperature of 50-60°C; 5) The alloy ingot after solution treatment is subjected to aging treatment at a temperature of 150°C for 6 h, followed by air cooling to room temperature.
[0030] Example 3 According to the weight percentage of the constituent elements, Mg: 8.5%, Si: 3.0%, Fe: 0.4%, Ti: 0.15%, Te: 0.1%, Ho: 0.5%, Tb: 0.1%, and the balance is Al. The specific alloy preparation process is as follows: 1) According to the designed alloy composition, pure aluminum is first placed in a graphite crucible, and the temperature of the resistance furnace is set to 750°C. After the aluminum is completely melted, other master alloys except pure magnesium and rare earth element master alloys are added, and then the temperature of the resistance furnace is lowered to 710°C, pure magnesium wrapped in aluminum foil is added, and a layer of covering agent (KCl + NaCl, mass fraction 1:1) is sprinkled on it. After the pure magnesium is completely melted, hexachloroethane is added for degassing, and then Al-Ho and Al-Tb master alloys are added to obtain melt 1; 2) Take the melt 1 of step 1), add the composite carbide preform, the mass ratio of the preform to the melt 1 is 1:20, insert the ultrasonic vibrator 80 mm below the melt, start the ultrasonic vibration for 0.5 h to obtain the melt 2, the maximum amplitude of the ultrasonic vibration is 50 nm, and the vibration frequency is 20 kHz; 3) Take melt 1 and keep it warm for 10 minutes, pour it into the die-casting storage cylinder with a feeding spoon for die-casting, the pouring temperature is 700-720°C, the mold temperature is 180-200°C, the injection pressure is 85Mpa, the injection time is 3s, the cooling time is 2s, the mold retention time is 10s, and die-cast into aluminum alloy plate ingots; 4) subjecting the prepared alloy ingot to a solution treatment at a solution temperature of 480°C for 8 hours, and then rapidly cooling it in water at a temperature of 50-60°C; 5) The alloy ingot after solution treatment is subjected to aging treatment at a temperature of 150°C for 6 h, followed by air cooling to room temperature.
[0031] Example 4 According to the weight percentage of the constituent elements, Mg: 8.5%, Si: 3.0%, Fe: 0.4%, Ti: 0.15%, Sn: 0.3%, Bi: 0.1%, Ir: 0.3%, Ta: 0.5%, Te: 0.1%, Ho: 0.5%, Tb: 0.1%, and the balance is Al. The specific alloy preparation process is as follows: 1) The master alloys used are Al-20Si, Al-10Fe, Al-10Ti, Al-50Sn, Al-10Bi, Al-10Ir, Al-10Ta, and Al-5Te. According to the designed alloy composition, pure aluminum is first placed in a graphite crucible, and the temperature of the resistance furnace is set to 750°C. After the aluminum is completely melted, the above master alloys are added, and then the temperature of the resistance furnace is lowered to 710°C, pure magnesium wrapped in aluminum foil is added, and a layer of covering agent (KCl + NaCl, mass fraction 1:1) is sprinkled on it. After the pure magnesium is completely melted, hexachloroethane is added for degassing, and then Al-Ho and Al-Tb master alloys are added to obtain melt 1; 2) Take the melt 1 of step 7), add the composite carbide preform, the mass ratio of the preform to the melt 1 is 1:20, insert the ultrasonic vibrator 80 mm below the melt, start the ultrasonic vibration for 0.5 h to obtain the melt 2, the maximum amplitude of the ultrasonic vibration is 50 nm, and the vibration frequency is 20 kHz; 3) Use a feeding spoon to take the melt 2 and pour it into the die casting storage cylinder to die-cast the alloy casting. The pouring temperature is 700-720°C, the mold temperature is 180-200°C, the injection pressure is 85Mpa, the injection time is 3s, the cooling time is 2s, and the mold retention time is 10s; 4) subjecting the prepared alloy ingot to a solution treatment at a solution temperature of 480°C for 8 hours, and then rapidly cooling it in water at a temperature of 50-60°C; 5) The alloy ingot after solution treatment is subjected to aging treatment at a temperature of 150°C for 6 hours and cooled in air.
[0032] Comparative Example 1 According to the weight percentage of the constituent elements, Mg: 8.5%, Si: 3.0%, Fe: 0.4%, Ti: 0.15%, and the balance is Al. The specific alloy preparation process is as follows: 1) According to the designed alloy composition, pure aluminum is first placed in a graphite crucible, and the temperature of the resistance furnace is set to 750°C. After the aluminum is completely melted, other intermediate alloys are added, and then the temperature of the resistance furnace is lowered to 710°C, pure magnesium wrapped in aluminum foil is added, and a layer of covering agent (KCl + NaCl, mass fraction 1:1) is sprinkled on it. After the pure magnesium is completely melted, hexachloroethane is added for degassing to obtain melt 1; 2) Take the melt 1 of step 1), add the composite carbide preform, the mass ratio of the preform to the melt 1 is 1:20, insert the ultrasonic vibrator 80 mm below the melt, start the ultrasonic vibration for 0.5 h to obtain the melt 2, the maximum amplitude of the ultrasonic vibration is 50 nm, and the vibration frequency is 20 kHz; 3) Take melt 1 and keep it warm for 10 minutes, pour it into the die-casting storage cylinder with a feeding spoon for die-casting, the pouring temperature is 700-720°C, the mold temperature is 180-200°C, the injection pressure is 85Mpa, the injection time is 3s, the cooling time is 2s, the mold retention time is 10s, and die-cast into aluminum alloy plate ingots; 4) subjecting the prepared alloy ingot to a solution treatment at a solution temperature of 480°C for 8 hours, and then rapidly cooling it in water at a temperature of 50-60°C; 5) The alloy ingot after solution treatment is subjected to aging treatment at a temperature of 150°C for 6 h, followed by air cooling to room temperature.
[0033] Comparative Example 2 According to the weight percentage of the constituent elements, Mg: 8.5%, Si: 3.0%, Fe: 0.4%, Ti: 0.15%, Sn: 0.3%, Bi: 0.1%, Ir: 0.3%, Ta: 0.5%, Te: 0.1%, Ho: 0.5%, Tb: 0.1%, and the balance is Al. The specific alloy preparation process is as follows: 1) According to the designed alloy composition, pure aluminum was first placed in a graphite crucible, and the temperature of the resistance furnace was set to 750°C. After the aluminum was completely melted, other master alloys were added. Then the temperature of the resistance furnace was lowered to 710°C, pure magnesium wrapped in aluminum foil was added, and a layer of covering agent (KCl + NaCl, mass fraction 1:1) was sprinkled on it. After the pure magnesium was completely melted, hexachloroethane was added for degassing, and then Al-Ho and Al-Tb master alloys were added. After 20 minutes, the slag was removed to obtain melt 1; 2) Take the melt 1 of step 1), add the composite carbide preform, the mass ratio of the preform to the melt 1 is 1:20, insert the ultrasonic vibrator 80 mm below the melt, start the ultrasonic vibration for 0.5 h to obtain the melt 2, the maximum amplitude of the ultrasonic vibration is 50 nm, and the vibration frequency is 20 kHz; 3) Take melt 1 and keep it warm for 10 minutes, pour it into the die-casting storage cylinder with a feeding spoon for die-casting, the pouring temperature is 700-720°C, the mold temperature is 180-200°C, the injection pressure is 85Mpa, the injection time is 3s, the cooling time is 2s, the mold retention time is 10s, and die-cast into aluminum alloy plate ingots; 4) subjecting the prepared alloy ingot to a solution treatment at a solution temperature of 480°C for 8 hours, and then rapidly cooling it in water at a temperature of 50-60°C; 5) The alloy ingot after solution treatment is subjected to aging treatment at a temperature of 150°C for 6 h, followed by air cooling to room temperature.
[0034] Comparative Example 3 According to the weight percentage of the constituent elements, Mg: 8.5%, Si: 3.0%, Fe: 0.4%, Ti: 0.15%, Sn: 0.3%, Bi: 0.1%, Ir: 0.3%, Ta: 0.5%, Te: 0.1%, Ho: 0.5%, Tb: 0.1%, and the balance is Al. The specific alloy preparation process is as follows: 1) According to the designed alloy composition, pure aluminum is first placed in a graphite crucible, and the temperature of the resistance furnace is set to 750°C. After the aluminum is completely melted, other intermediate alloys are added, and then the temperature of the resistance furnace is lowered to 710°C, pure magnesium wrapped in aluminum foil is added, and a layer of covering agent (KCl + NaCl, mass fraction 1:1) is sprinkled on it. After the pure magnesium is completely melted, hexachloroethane is added for degassing to obtain melt 1; 2) Take the melt 1 of step 1), add the TaC / HfC preform, the mass ratio of the preform to the melt 1 is 1:20, insert the ultrasonic vibrator 80 mm below the melt, start the ultrasonic vibration for 0.5 h to obtain the melt 2, the maximum amplitude of the ultrasonic vibration is 50 nm, and the vibration frequency is 20 kHz; 3) Take melt 1 and keep it warm for 10 minutes, pour it into the die-casting storage cylinder with a feeding spoon for die-casting, the pouring temperature is 700-720°C, the mold temperature is 180-200°C, the injection pressure is 85Mpa, the injection time is 3s, the cooling time is 2s, the mold retention time is 10s, and die-cast into aluminum alloy plate ingots; 4) subjecting the prepared alloy ingot to a solution treatment at a solution temperature of 480°C for 8 hours, and then rapidly cooling it in water at a temperature of 50-60°C; 5) The alloy ingot after solution treatment is subjected to aging treatment at a temperature of 150°C for 6 hours, followed by air cooling to room temperature; The manufacturing process of TaC / HfC prefabricated block is as follows: 1) Alkaline washing: Heat 300 mL of 0.5 mol / L KOH solution in a water bath. When the temperature rises to 95°C, add 50 g of TaC powder and HfC powder. The mass percentage of TaC powder and HfC powder is 1:1. Stir at this temperature for 30 min and filter. 2) Acid washing: Put the TaC powder and HfC powder after the previous step of alkaline washing into 0.1 mol / L HNO 3 Soak in the solution for 10 minutes, filter and dry; 3) Ball milling mixed powder: take the raw materials in step 3) and ball mill them for 6 to 8 hours under argon protection environment, the ball milling speed is 600 to 800 r / min, the ball-to-material ratio is 1:8, and butanone is added as a grinding dispersant in an amount of 15% to 20% of the total weight of the raw materials. After grinding, a mixed powder is obtained, in which the mass fraction of carbide powder is 15% to 20%; 4) Vacuum drying: the mixed powder after ball milling in step 4) is placed in a vacuum drying oven and dried at 60° C. for 10 to 12 hours to remove the dispersant to obtain a dry mixed powder; 5) Spark plasma sintering: The composite powder of step 5) is placed in a graphite mold with a diameter of 20 mm, and spark plasma sintering is performed in a spark plasma sintering furnace under a nitrogen protective atmosphere. The sintering pressure is 50 MPa, the sintering temperature is 530°C, the holding time is 6 min, and the furnace is cooled to prepare a number of composite carbide preforms with a size of φ20 mm×10 mm, and the density is controlled between 85-90%.
[0035] Comparative Example 1: The difference from the embodiment is that it only contains Al, Mg, Si, Fe, and Ti, and no other elements for modification are added.
[0036] Comparative Example 2: The difference from the embodiment is that no composite carbide prefabricated block is added before die casting.
[0037] Comparative Example 3: The difference from the embodiment is that a composite carbide prefabricated block of un-iron-plated and ball-milled mixed aluminum powder is added before die-casting.
[0038] Comparison of Alloy Properties The Al-Mg-Si-Fe-Ti-Re alloy plates obtained in the embodiments and comparative examples were tested for corrosion resistance and fluidity, respectively, wherein the corrosion resistance test method was formulated in accordance with GB / T 10125-2021 "Artificial atmosphere corrosion test salt spray test". The test conditions are as follows: the temperature of the salt spray test chamber is 35±2°C, the temperature of the air saturator is 45°C, the humidity is 100%, the test solution is (50±5) g / L NaCl aqueous solution, the water is deionized water, and the test time is 480h. The fluidity is characterized by casting a spiral specimen and measuring its flow length. The test results of the corrosion resistance and fluidity of each example are shown in Table 1.
[0039] Table 1 Test results of mechanical properties, corrosion resistance and fluidity of various examples
[0040] By comparing Example 1 with Comparative Example 1, it can be seen that adding appropriate amounts of Sn and Bi can effectively improve the casting fluidity of the alloy; By comparing Example 2 with Comparative Example 1, it can be seen that adding appropriate amounts of Ir and Ta increases the potential of the aluminum matrix and improves the corrosion resistance of the alloy; By comparing Example 3 with Comparative Example 1, it can be seen that the role of Te, Ho and Tb is mainly to refine the grain size and improve the strength of the alloy.
[0041] By comparing Example 4 with Comparative Example 2, it can be seen that adding an appropriate amount of TaC / HfC has the combined effects of grain refinement and dispersion strengthening, and effectively improves the room temperature mechanical properties of the alloy.
[0042] By comparing Example 4 with Comparative Example 3, it can be seen that the iron plating and ball-milled mixed aluminum powder in the process of preparing the prefabricated block improve the strength and comprehensive mechanical properties of the alloy by refining the grains and enhancing the dispersion strengthening phase.
[0043] The above is a further detailed description of the present invention, which should not be regarded as a limitation on the specific implementation of the present invention. For ordinary technicians in the technical field to which the present invention belongs, simple deduction or replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A high-strength, corrosion-resistant die-cast Al-Mg-Si-Fe-Ti-Re alloy, characterized in that: In terms of mass percentage, the alloy comprises the following composition: Mg 8.0~9.0%, Si 2.5~3.5%, Fe 0.3~0.5%, Ti 0.1~0.2%, Sn 0.2~0.4%, Bi 0.05~0.15%, Re 0.3~0.5%, and the balance is Al and inevitable impurities.
2. The alloy according to claim 1, characterized in that In terms of mass percentage, the alloy contains the following rare metals: Ir 0.2-0.4%, Ta 0.3-0.5%, Te 0.05-0.15%.
3. The alloy according to claim 1, characterized in that In terms of mass percentage, the alloy contains the following rare metals: Ho 0.3-0.5%, Tb 0.05-0.15%.
4. The method for preparing the Al-Mg-Si-Fe-Ti-Re alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Melt: After melting the ingredients according to the alloy composition, a covering agent and a degassing agent are added to obtain a melt 1; 2) Ultrasonic mixing of melt: melt 1 from step 1) is added with the composite carbide preform, and melt 2 is obtained after ultrasonic vibration for 0.5 to 1 h; 3) Ingot casting treatment: taking the melt 2 for die casting treatment, solution treatment and aging treatment to obtain the high-strength and corrosion-resistant die-cast Al-Mg-Si-Fe-Ti-Re alloy.
5. The preparation method according to claim 4, characterized in that: In the step 2), the mass ratio of the composite carbide prefabricated block to the melt 1 is 1:(19.5-20.5).
6. The preparation method according to claim 4, characterized in that: The preparation method of the composite carbide prefabricated block added in step 2) is as follows: 1) Cleaning: Mix TaC powder and HfC powder in a mass ratio of (0.95-1.05):1, perform alkali washing and acid washing in sequence, filter and dry to obtain composite carbide; 2) Iron plating: Fe2(SO4)3·9H2O solution and NaBH4 solution are heated and mixed to obtain a plating solution, and then NaHCO3 solution is added until the plating solution is clarified, and then dopamine hydrochloride, composite carbide, and HCHO solution are added to react for 30 to 60 minutes to obtain iron-plated carbide powder; 3) Ball milling mixed powder: ball milling the iron-plated carbide powder in step 2), then mixing it with aluminum powder, and drying to obtain a mixed powder of iron-plated carbide and aluminum powder, wherein the mass fraction of the iron-plated carbide powder is 15% to 20%; 4) The mixed powder in step 3) is subjected to spark plasma sintering and cooled to obtain a composite carbide preform having a size of φ20 mm×10 mm, and the density thereof is controlled between 85% and 90%.
7. The preparation method according to claim 4, characterized in that: The particle size of the TaC powder used in step 1) is in the range of 1000-1400 mesh, wherein the particle size of the HfC powder is in the range of 900-1200 mesh.
8. The preparation method according to claim 4, characterized in that: The pouring temperature of the die casting process is 700-720°C.
9. The preparation method according to claim 4, characterized in that: The solution operation is as follows: the solution temperature is 480-500° C., the heat preservation time is 8-12 hours, and then it is quickly placed in water with a temperature of 50-60° C. for cooling.
10. The preparation method according to claim 4, characterized in that: The aging treatment operation is as follows: the aging treatment temperature is 140-160° C., the heat preservation time is 6-8 h, and then air-cooling to room temperature.